Private Schools in Canada and the USA: Contrasts and Commonalities - Allison, Derek J.; Van Pelt, Deani Neven; Hasan, Sazid; Bosetti, Lynn (Journal of Applied Business and Economics, 2017)
Characteristics of private schools in Canada and the USA are compared using NCES Private School Universe Survey data, previously unavailable Canadian data, and selected survey results from PISA 2015. Differences are noted between curriculum levels, average enrollments, religious orientations and school autonomy. Five Canadian provinces offer direct funding to private schools whereas various US states channel funds to private schools through voucher or similar schemes. While the proportion of students attending private schools in Canada has been increasing, the growth of charter schools in the US appears to have contributed to a decline in US private school enrollments.